Problem-solving training: assessing the feasibility and acceptability of delivering and evaluating a problem-solving training model for front-line prison staff and prisoners who self-harm - Gerry Richardson; Allan House; Amanda Farrin; Alexandra Wright-Hughes; Joanne Greenhalgh; Amanda Perry; Mitchell Glenn Waterman; Ann Kathryn Hopton; Nat Wright (BMJ Open)
Objectives Problem-solving skills training is adaptable, inexpensive and simple to deliver. However, its application with prisoners who self-harm is unknown. The study assessed the feasibility and acceptability of a problem-solving training (PST) intervention for prison staff and prisoners who self-harm, to inform the design of a large-scale study.Design and setting A mixed-methods design used routinely collected data, individual outcome measures, an economic protocol and qualitative interviews at four prisons in Yorkshire and Humber, UK.Participants (i) Front-line prison staff, (ii) male and female prisoners with an episode of self-harm in the previous 2 weeks.Intervention The intervention comprised a 1 hour staff training session and a 30 min prisoner session using adapted workbooks and case studies.Outcomes We assessed the study processes—coverage of training; recruitment and retention rates and adequacy of intervention delivery—and available data (completeness of outcome data, integrity of routinely collected data and access to the National Health Service (NHS) resource information). Prisoner outcomes assessed incidence of self-harm, quality of life and depression at baseline and at follow-up. Qualitative findings are presented elsewhere.Results Recruitment was higher than anticipated for staff n=280, but lower for prisoners, n=48. Retention was good with 43/48 (89%) prisoners completing the intervention, at follow-up we collected individual outcome data for 34/48 (71%) of prisoners. Access to routinely collected data was inconsistent. Prisoners were frequent users of NHS healthcare. The additional cost of training and intervention delivery was deemed minimal in comparison to ‘treatment as usual’. Outcome measures of self-harm, quality of life and depression were found to be acceptable.Conclusions The intervention proved feasible to adapt. Staff training was delivered but on the whole it was not deemed feasible for staff to deliver the intervention. A large-scale study is warranted, but modifications to the implementation of the intervention are required.